2017
DOI: 10.1111/jch.13038
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein ratios are better than conventional lipid parameters in predicting arterial stiffness in young men

Abstract: Although dyslipidemia is associated with cardiovascular disease, there are conflicting data about the role of serum lipids and their ratios in promoting arterial stiffness. The authors aimed to compare serum lipid profiles to predict arterial stiffness, which was assessed by brachial‐ankle pulse wave velocity in young Chinese men. A total of 1015 participants aged 18 to 44 years without serious comorbidities were recruited for conventional detection. Anthropometrics, brachial‐ankle pulse wave velocity, serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 44 publications
4
56
0
Order By: Relevance
“…In the current issue of the Journal, Wen and coworkers assessed the relationships of lipids and their ratio with baPWV in a wide group of young Chinese men. They found that lipid ratios were better associated with baPWV than conventional single lipid parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current issue of the Journal, Wen and coworkers assessed the relationships of lipids and their ratio with baPWV in a wide group of young Chinese men. They found that lipid ratios were better associated with baPWV than conventional single lipid parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They found that lipid ratios were better associated with baPWV than conventional single lipid parameters. In multivariate analyses, the triglyceride (TG)/high‐density lipoprotein cholesterol (HDL‐C) ratio appears to be most closely associated with arterial stiffness, followed by the non–HDL‐C/HDL‐C ratio, and then total cholesterol/HDL‐C and TG …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG/HDL-C is also regarded as a strong indicator of increased small dense low-density lipoprotein particles which, compared with larger low-density lipoprotein particles, exhibit a greater negative impact on endothelial stiffness and function and arterial distensibility. [5][6][7][8][9][10] In the current study, the investigators report the use of the METS-IR in a population at risk for CVD correlates with arterial stiffness and is a predictor of incident hypertension. 11 The inclusion of BMI as a surrogate for visceral adiposity in the METS-IR is relevant as recent data support a strong link between adipose tissue remodeling of both visceral fat and perivascular fat in the development of vascular IR and stiffness (Figure 1).…”
Section: Introductionmentioning
confidence: 94%
“…Plasma TG and HDL‐C concentrations are related to insulin‐mediated glucose disposal, and many studies suggest that the TG/HDL‐C ratio provides a simple way to identify individuals who are IR and are at increased cardiometabolic risk. TG/HDL‐C is also regarded as a strong indicator of increased small dense low‐density lipoprotein particles which, compared with larger low‐density lipoprotein particles, exhibit a greater negative impact on endothelial stiffness and function and arterial distensibility …”
mentioning
confidence: 99%